Avian gene trees, landscape evolution, and geology: towards a modern synthesis of Amazonian historical biogeography? - (:unkn) unknown (Springer Verlag, 2007)
Recent studies have improved our understanding of Amazonian geological history during the late Tertiary and Quaternary, two periods regarded as critical for the recent diversification of the Amazonian avifauna. The notion that geologically older and more stable areas of Amazonia (such as the Brazilian and Guianan shields) functioned as ‘‘species-pumps’’, whereas geologically more dynamic areas (such as the western Amazonian lowlands) mostly ‘‘captured’’ part of the diversity generated nearby, was supported by a recent phylogeographic study focusing on a species complex of the genus Xiphorhynchus (Dendrocolaptidae). Here, we review several additional molecular datasets to assess whether this historical scenario can be extended to other lineages of Amazonian birds as well. The datasets reviewed indicated that most lineages of upland forest species found nowadays in western Amazonia are associated with more basal lineages from the Brazilian shield, Guianan shield, and the Andes, indicating a more recent history in this geologically dynamic region. Conversely, lineages associated with seasonally flooded forests seem to have an ancient history in western Amazonia, apparently expanding over the geologically more stable areas only recently. Most sister taxa of the lineages reviewed exhibited levels of pairwise sequence divergence consistent with splitting events dating back to a time frame stretching from the late Miocene to the early Pleistocene, a period when significant physiographic and landscape changes took place in Amazonia. When interpreted together, all the studies reviewed provide evidence that geology and landscape evolution are tightly linked with the timing and mode of differentiation of Amazonian birds.
Keywords: Amazônia; Avifauna; Geology; Historical biogeography; Molecular systematics; Sistemática molecular; Biogeografia; Geologia; Aves; Birds